Wilhelmy balance characterization beyond contact angles: Differentiating leaching from nanosurface reorganization and optimizing surface modification. (5th May 2017) - Wang, Chenyu; Nair, Sithara; Wynne, Kenneth J.
Abstract: Over and above measurements of contact angles, this article provides examples from our work that emphasize unexpected wetting behavior using the Wilhelmy Plate (WP) method. These findings either would not have been noticed by conventional sessile drop methods or might have been dismissed due to deviations associated with measurements or sample-to-sample variations in surface composition. The examples chosen for this article include: (1) Wilhelmy plate force distance curves providing a sensitive measure for the detection of leaching or diffusion of species from polydimethylsiloxane elastomeric coatings, (2) A Dynamic Contact Angle (DCA) investigation of a polyurethane to establish whether changes in CAs vs immersion time were due to leaching of substances that changed the surface tension of water or to nanosurface reorganization of polymer chains, (3) Changing network formation conditions that give low or high receding contact angles (θR ) and "sticky or slippery" wetting of water drops on a widely used Sylgard 184 silicone coating as well as the impact of θR on ice adhesion and (4) Polymer surface modification for introducing special functionality via a modifier is shown to depend on a balance of miscibility and immiscibility that resulted in an unexpected "more is less" dependence on concentration for a fluorous modifier and a condensation cured silicone. Graphical abstract: Highlights: A review of our work using the Wilhelmy Plate (WP) method for contact angles (CAs). The WP-CA method provides unique insight. Leaching of polymer contaminants is easily determined. Contact angle hysteresis and cycle-to-cycle variations are highlighted.